Picosecond laser sintering of silver paste printed by laser induced forward transfer. (March 2021) - Liu, Qi; Xu, Bin; Zhang, Yongnian; Wang, Xinwei; Mei, Xinliang; Wang, Xingsheng
Highlights: LIFT followed by laser sintering was used to fabricate conductive Ag lines. A TTM was established to simulate picosecond laser sintering process. A merged morphology induced by laser sintering improved the electrical conductivity. The excess heat accumulation led to the oxidation of the silver paste. Abstract: In this study, the fabrication of conductive silver lines through the combination of laser induced forward transfer (LIFT) printing and laser sintering using the same picosecond laser is investigated. Continuous lines were firstly printed by LIFT of silver paste using the selected parameters, and then the effects of processing parameters on the morphology and conductivity of the printed line during picosecond laser sintering process were studied. A classical axisymmetric two-temperature model was established to further analyze the temperature distributions during the laser sintering process. Experimental results indicated that as the pulse energy and pulse number increased, the surface structures of the printed silver lines merged together due to the increasing temperature, leading to the improvement of the conductivity. However, the excess heat accumulation led to the oxidation of the silver paste and induced the reduction of the conductivity. The silver line with lowest resistivity of 1.4 × 10 −7 Ω·m was obtained at pulse energy of 1.3 μJ, frequency of 0.8 MHz and scanning speed of 7 mm/s. The simulation results of the temperature evolution were accordant with the experimental results, and both of them exhibited the feasibility and effectiveness of the fabrication of conductive line using the developed method.